An In-Depth Analysis of the Oral Reading Comprehension of the Grade 7 Students of Liceo de Pulilan Colleges Inc - Bugauisan Julie Ann L; Caasi Jr Richard E; Isleta Angelica Joy M; Laoyon Gresa J; Reyes Henderson DN; De Jesus Dennis A (Yayasan Adra Karima Hubbi, 2024)
Background. The increasingly complex cybersecurity crisis demands faster and more efficient solutions, so the implementation of artificial intelligence (AI) in cybersecurity crisis management is becoming increasingly relevant. Purpose. This study aims to evaluate how AI can improve effectiveness in detecting and responding to cyber threats. Method. The research method uses a mixed approach, which involves quantitative data analysis from cyber attack simulations and qualitative interviews with cybersecurity experts. Results. The results show that AI significantly accelerates threat detection and improves response efficiency, with a success rate of up to 85%. AI is also capable of analyzing big data in a short period of time, but it still has limitations in dealing with unexpected attacks. Conclusion. The study emphasized the need for targeted interventions and instructional improvements to bridge these gaps and foster a higher level of literacy among students. Ultimately, the research contributed to developing effective educational policies and practices that aimed to enhance reading skills, supporting students' academic success and lifelong learning potential.